2010
DOI: 10.2478/v10043-010-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvesting Time and Area on Carcass Weight of the European Fallow Deer (Dama damaL.)

Abstract: The aim of the present study was to characterise carcass weights of the European fallow deer harvested during the hunting seasons 2001/2002-2004/2005 in four provinces of northern Poland. The average carcass weights of bucks, does and fawns harvested throughout the study period in the given area were 48.81 kg, 32.51 kg and 20.79 kg, respectively. Carcass weights of the fallow deer were found to be higher in provinces with a high percentage of farmland and lower in provinces with a high percentage of woodland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The seasonal patterns of the changes body weight and body composition in deer are associated with the changes in the percentage of body fat, protein, and water. In the winter season, the body fat and protein reserves depend on the pre-winter and post-winter levels of these components [ 13 , 34 ]. In the present study, the proportion of fat was significantly greater in the carcasses, as well as in the individual carcass parts, of the deer obtained in winter compared to those from the summer season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seasonal patterns of the changes body weight and body composition in deer are associated with the changes in the percentage of body fat, protein, and water. In the winter season, the body fat and protein reserves depend on the pre-winter and post-winter levels of these components [ 13 , 34 ]. In the present study, the proportion of fat was significantly greater in the carcasses, as well as in the individual carcass parts, of the deer obtained in winter compared to those from the summer season.…”
Section: Discussionmentioning
confidence: 99%
“…Although no effect of the season on the offal weight was found in our study, many researchers have observed seasonal fluctuations in the weight of some internal organs from wild deer. The variations in the weight of the gastrointestinal tract are caused by seasonal changes in the degree of filling the rumen with green forage [ 7 , 13 , 34 ]. This phenomenon is connected to the reduction in appetite in free-living animals and the decreased voluntary intake of feed [ 14 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation